The Influence of Indoor Environment in Respiratory Health and Quality of Life of Older People Living in Elderly Care Centers - Mendes, Ana (2017)
The mean age of the European population is rising and percentage of adults aged 65 years and older is projected to increase from 16% in 2000 to 20% in 2020. It has been estimated that older subjects spend approximately 19 to 20 h/day indoors. Older individuals may be particularly at risk for detrimental effects from pollutants, even at low concentrations, due to reduced immunological defenses and multiple underlying chronic diseases. This cross-sectional study explored environmental variables and buildings characteristics in 22 elderly care centers (ECC) out of a total of 58 institutions in Porto, Portugal.